Razzle Dazzle Unicorn : Another Phoebe and Her Unicorn Adventure - Simpson, Dana (Kansas City, Missouri Andrews McMeel Publishing, 2016)
Razzle Dazzle Unicorn is the fourth volume in Dana Simpson's Phoebe and Her Unicorn series, following the adventures of Phoebe and her narcissistic unicorn BFF, Marigold Heavenly Nostrils. The graphic novel covers roughly eight months of school, summer camp, and magical mishaps, featuring "sparkle fever," jealous frenemies, and a disappearing room.
English
Keywords: Comics; Humor; Graphic Novel; Fantasy Fiction